2022
DOI: 10.3389/fonc.2022.922928
|View full text |Cite
|
Sign up to set email alerts
|

Receptor tyrosine kinase (RTK) targeting in pediatric high-grade glioma and diffuse midline glioma: Pre-clinical models and precision medicine

Abstract: Pediatric high-grade glioma (pHGG), including both diffuse midline glioma (DMG) and non-midline tumors, continues to be one of the deadliest oncologic diagnoses (both henceforth referred to as “pHGG”). Targeted therapy options aimed at key oncogenic receptor tyrosine kinase (RTK) drivers using small-molecule RTK inhibitors has been extensively studied, but the absence of proper in vivo modeling that recapitulate pHGG biology has historically been a research challenge. Thankfully, there have been many recent ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 124 publications
0
10
0
Order By: Relevance
“…Three drugs emerged as OncoTreat-predicted inhibitors of OPC states, respectively, including trametinib (highly selective inhibitor of the mitogen-activated protein kinase enzymes MEK1 and MEK2 68 ), mocetinostat (an HDAC inhibitor with highest affinity to HDAC1, but also targeting HDAC2, 3 and 11 69 ), and dinaciclib (a potent small molecule cyclin-dependent kinase inhibitor targeting CDK2, CDK5, CDK1 and CDK9 70 ). Two additional drugs emerged as OncoTarget-predicted inhibitors of OPC and OC states, respectively, including etoposide (a TOP2 inhibitor, targeting both TOP2 isoforms: TOP2A and TOP2B 71 ), and avapritinib (a CNS-penetrant PDGFRA inhibitor 72 ). Similarly, two drugs emerged as OncoTreat-predicted inhibitors of AC states, including venetoclax (a highly selective BCL2 inhibitor 73 ) and ruxolitinib (an ATP-competitive JAK1/2 inhibitor 73 ) and an additional two were predicted by OncoTarget, including larotrectinib (a highly selective TRK inhibitor 74 ) and napabucasin (a STAT3 inhibitor 75 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three drugs emerged as OncoTreat-predicted inhibitors of OPC states, respectively, including trametinib (highly selective inhibitor of the mitogen-activated protein kinase enzymes MEK1 and MEK2 68 ), mocetinostat (an HDAC inhibitor with highest affinity to HDAC1, but also targeting HDAC2, 3 and 11 69 ), and dinaciclib (a potent small molecule cyclin-dependent kinase inhibitor targeting CDK2, CDK5, CDK1 and CDK9 70 ). Two additional drugs emerged as OncoTarget-predicted inhibitors of OPC and OC states, respectively, including etoposide (a TOP2 inhibitor, targeting both TOP2 isoforms: TOP2A and TOP2B 71 ), and avapritinib (a CNS-penetrant PDGFRA inhibitor 72 ). Similarly, two drugs emerged as OncoTreat-predicted inhibitors of AC states, including venetoclax (a highly selective BCL2 inhibitor 73 ) and ruxolitinib (an ATP-competitive JAK1/2 inhibitor 73 ) and an additional two were predicted by OncoTarget, including larotrectinib (a highly selective TRK inhibitor 74 ) and napabucasin (a STAT3 inhibitor 75 ).…”
Section: Resultsmentioning
confidence: 99%
“…5,6 Erdafitinib is expected to have sufficient blood-brain barrier penetration. 17 Current literature reports on seven paediatric patients treated with FGFR inhibitors to date, five with Debio1347 4…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, certain high‐risk tumour types such as EPN have been shown to exhibit FGFR activation 5,6 . Erdafitinib is expected to have sufficient blood–brain barrier penetration 17 . Current literature reports on seven paediatric patients treated with FGFR inhibitors to date, five with Debio1347 4 and two with erdafitinib as part of the RAGNAR study 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, preclinical studies have shown that Imatinib can prevent the PI3K/mTOR signaling pathway or MAPK signaling pathway by docking with PDGFRA. It can effectively inhibit tumor growth, exert anti-tumor activity, and be proven effective in pediatric HGG with PDGF pathway alterations ( Schwark et al, 2022 ). In line with this, a small RCT study found that patients with glioblastoma responded frequently to the combination of hydroxyurea and imatinib ( Joensuu et al, 2005 ; Mantica et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study selected Imatinib as the reference drug. However, Imatinib has significant therapeutic limitations, with developmental toxicity and the risk of intratumoral hemorrhage as side effects ( Schwark et al, 2022 ). The screening of more desirable inhibitors of PDGFRA is therefore essential for the treatment of HGG.…”
Section: Discussionmentioning
confidence: 99%